Revision of the Amazonian species of Syneches Walker (Diptera, Hybotidae, Hybotinae) - Menezes, Isis Sá; Ale-Rocha, Rosaly (Zootaxa, 2016)
A revision of the Amazonian species of Syneches Walker resulted in the re-description of four species and the description of nine new species: Syneches amazonicus sp. nov., S. angulatus sp. nov., S. applanatus sp. nov., S. bilobatus sp. nov., S. equatoriensis sp. nov., S. exilis sp. nov., S. maculosum sp. nov., S. striatus sp. nov., S. tenebricus sp. nov., and two new synonymies: S. quadricinctus (Fabricius, 1805) = S. curvipes (Fabricius, 1805) and S. hispidus Ale-Rocha & Vieira, 2008 = S. repletus Bezzi, 1909. The male of S. fuscescens Bezzi and the female of S. annulipes Bezzi are described and their terminalia are illustrated. Geographic records for S. annulipes Bezzi, S. curvipes (Fabricius), S. fuscescens Bezzi, S. manaos Smith, S. moraballi Smith, S. rafaeli Ale-Rocha & Vieira, S. repletus Bezzi and S. walkeri Smith and an identification key for the species recorded in the Amazon are provided. Copyright © 2016 Magnolia Press.
Keywords: Anatomy And Histology; Animals; Animals Dispersal; Animals Structures; Body Size; Classification; Diptera; Female; Growth, Development And Aging; Male; Muscidae; Organ Size; Animals Distribution; Animals Structures; Animal; Body Size; Diptera; Female; Male; Muscidae; Organ Size